2018
DOI: 10.1016/j.anifeedsci.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary supplementation with sunflower oil and quebracho tannins on growth performance and meat fatty acid profile of Awassi lambs

Abstract: A B S T R A C TThe influence of dietary supplementation with quebracho tannins (QT) or/and sunflower oil (SF) on growth performance and fatty acid profile in meat of Awassi lambs was studied. Seventy-two lambs were assigned randomly to nine diets (8 per group) in the experiment following a 3 2 factorial design with all possible combinations of two factors, SF and QT each at three levels i.e. 0 (control), 20 or 40 g/kg diet DM. A significant SF × QT interaction was observed on the conjugated linoleic acid conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 30 publications
(27 reference statements)
2
13
0
1
Order By: Relevance
“…It is not possible to affirm this, however, if the experimental length were longer, it is possible that we could have observed effects of supplementation on body weight and weight gain, as were observed by researchers using 0.8% of quebracho in lamb diets [9]. A similar result was also reported when quebracho was included at 40 g of quebracho/kg (corresponding to 0.4%) of dry matter, significantly increasing the average daily gain in lambs, compared to control diets [15]. Researchers observed that the addition of chestnut tannins (0.5 and 1%) increased lamb growth under heat stress [16].…”
Section: Discussionsupporting
confidence: 81%
“…It is not possible to affirm this, however, if the experimental length were longer, it is possible that we could have observed effects of supplementation on body weight and weight gain, as were observed by researchers using 0.8% of quebracho in lamb diets [9]. A similar result was also reported when quebracho was included at 40 g of quebracho/kg (corresponding to 0.4%) of dry matter, significantly increasing the average daily gain in lambs, compared to control diets [15]. Researchers observed that the addition of chestnut tannins (0.5 and 1%) increased lamb growth under heat stress [16].…”
Section: Discussionsupporting
confidence: 81%
“…Further, tannin reduces enteric methane emission of ruminants through inhibition of methanogen and protozoa population [14]. Tannin inhibits biohydrogenation of polyunsaturated fatty acids in the rumen [15] and improves the deposition of these beneficial fatty acids in animal products [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of metabolizable protein to NI was found to be constant, ranging from 1.05 to 1.0 in control and 20 g SF + 40 g QT kg −1 , respectively. However, the diet comprising 20 g SF + 40 g QT kg −1 was found to have the highest average daily gain ( P = 0.11) among the diets tested. This finding shows that the quality of metabolizable protein might have a greater effect on the average daily gain compared to the quantity of metabolizable protein, which requires further investigation.…”
Section: Resultsmentioning
confidence: 91%
“…Moreover, the reduction of microbial biohydrogenation using condensed tannins (CT) would increase muscle Δ‐desaturase protein expression in sheep . Recently, Kamel et al reported that the inclusion of quebracho tannins (QT) and sunflower oil (SF) in lamb diets improved the meat contents with respect to healthy fatty acids without a negative effect on animal performance.…”
Section: Introductionmentioning
confidence: 99%